Effectiveness of Problem Based Learning Model Assisted by Youtube on Explanatory Text Writing Skills - Rosmiati, Ai; Wikanengsih (JLER (Journal of Language Education Research), 2025)
This study aims to test the effectiveness of the problem-based learning model supported by YouTube media in improving the skills of writing explanatory texts in class VIII students of Mts Plus An-nur Sumedang. Through a structured problem-solving process, students actively seek information from various relevant YouTube videos. The results of the study indicate; the application of the PBL learning model assisted by Youtube can improve the ability to write explanatory texts and the learning interest of class VIII students of MTs Plus An-Nuur Sumedang. This is evidenced by the increase in test scores, so the value of the ability to write explanatory texts of students before using the PBL model assisted by Youtube was 65,640 and after using the PBL model assisted by Youtube was 86,200. ability to write explanatory texts. This study concludes that the PBL learning model assisted by Youtube is effective in improving the ability to write explanatory texts and the learning interest of class VIII students of MTs Plus An-Nuur Sumedang.